Papillary Thyroid Microcarcinomas: Big Decisions for a Small Tumor - Haymart, Megan Rist (Ann Surg Oncol, 2009)
BACKGROUND: The clinical significance of papillary thyroid microcarcinoma (PTMC) is debated, and therefore the rise in incidence of PTMC creates management dilemmas. The following study evaluates factors influencing decisions to treat. MATERIALS AND METHODS: Between 1994 and 2007, 1361 patients underwent thyroid surgery at a single institution. Of these patients, 107 were diagnosed with PTMC. The type of surgical intervention, likelihood of referral to an endocrinologist, use of radioactive iodine, and administration of suppressive doses of levothyroxine (LT4) were analyzed in relation to patient and tumor characteristics. RESULTS: Multifocality and larger size were predictive of which patients underwent total thyroidectomy on multivariable logistic regression (P = .004 and P = .001, respectively). Larger mean tumor size, 0.62 ± 0.004 versus 0.34 ± 0.006 cm, was independently associated with increased likelihood of endocrine referral (P = .029). Multifocality, diagnosis via FNA preoperatively, larger mean size of PTMC, and endocrine referral were independently associated with increased likelihood of receiving radioactive iodine (RAI). On multivariable analysis, only total thyroidectomy and endocrine referral were independently associated with treatment with suppressive doses of LT4 (P = .001 and .001, respectively). In the 47 patients with unifocal PTMC <0.8 cm diameter, the mean size of tumor focus was larger in the subgroup undergoing total thyroidectomy (P = .004). Surprisingly, in these very low risk PTMC patients, the likelihood of RAI for remnant ablation was independently associated with younger patient age (P = .029). In the subgroup with unifocal <0.8 cm disease, the mean age of patients receiving RAI was 34 ± 3.3 years versus 48 ± 2.3 years in those not receiving RAI (P = .003). CONCLUSIONS: The decision tree in the management of PTMC is beginning at the time of surgery, and referral to endocrinology is associated with a more aggressive course. Younger age is predictive of RAI administration in the lowest-risk PTMC patients.